Neglected Financial Inclusion: A Study of the Financing Disparity of Ultra-Micro Enterprises in Indonesia - Fatmah Watty; Fatmawati Sungkawaningrum (Journal of Islamic Economics and Business, 2025)
The ultra-micro business sector, dominated by street vendors, daily traders, and itinerant traders, faces limited access to financing from formal financial institutions (LKF), especially for needs below IDR 3,000,000. This study aims to analyze the obstacles faced by ultra-micro business actors in accessing formal financing. Using a qualitative approach, data were collected through in-depth interviews with business actors and LKF representatives. The results of the study show that LKF has not optimally reached this segment due to regulatory and internal bureaucratic constraints. As a result, business actors turn to Informal moneylenders who offer high-interest loans, which actually increases the burden and worsens the inequality of financial access. This study emphasizes the importance of redesigning financial inclusion policies to be more adaptive, and fair in responding to the needs of ultra-micro business actors.